Effects of Heterotrophic Ammonia-oxidizing Bacteria on Yield and Water Use Efficiency of Dryland Maize - ZHAO Hongfei; WANG Xiaoling; CAO Jiawei; YU Hao; ZHOU Liju; TIAN Shishi (Shuitu Baochi Xuebao)
[Objective] To investigate the effects of inoculating heterotrophic ammonia-oxidizing bacteria (HAOB) on yield and water use efficiency of dryland maize. [Methods] A two-year field experiment was conducted in a drought-prone area using HAOB strain S2_8_1 as the test strain and maize as the plant material. Four treatments were set up, inoculation with HAOB strain without irrigation (DI), non-irrigated control (DCK), inoculation with HAOB strain with irrigation (WI), and irrigated control (WCK). [Results] Inoculation with the HAOB strain enhanced the nitrification rate in the rhizosphere soil and the photosynthetic rate of dryland maize, significantly promoted maize growth and increased the yield (p<0.05). The above-ground biomass at different stages and the yield at harvest in the DI and WI treatments were significantly higher than those in the DCK and WCK treatments, especially in the DI treatment. In both the drier 2022 and the wetter 2023, maize yields in the DI treatment exceeded those in the DCK and WCK treatments by at least 24.98%; in 2023, the yield of the DI treatment was comparable to that of the WI treatment, exceeding that of WCK by more than 11.29%. Additionally, inoculation of HAOB improved the water use efficiency of maize, with DI showing at least a 4.84% increase compared to DCK, and WI showing at least a 3.06% increase compared to WCK. The nitrification rates in the rhizosphere soil and the yields of DI and WI were similar, but DI did not require irrigation and had a higher water use efficiency. [Conclusion] The application of HAOB strains in dryland agriculture is an effective method for improving maize yield, and it can provide a new technological pathway and research direction for the development of dryland agriculture.